2013
DOI: 10.1002/cyto.a.22250
|View full text |Cite
|
Sign up to set email alerts
|

Determination of chitin content in fungal cell wall: An alternative flow cytometric method

Abstract: The conventional methods used to evaluate chitin content in fungi, such as biochemical assessment of glucosamine release after acid hydrolysis or epifluorescence microscopy, are low throughput, laborious, time-consuming, and cannot evaluate a large number of cells. We developed a flow cytometric assay, efficient, and fast, based on Calcofluor White staining to measure chitin content in yeast cells. A staining index was defined, its value was directly related to chitin amount and taking into consideration the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 25 publications
4
37
0
Order By: Relevance
“…Moreover, calcofluor white staining showed that VRC-treated cells emitted a more intense fluorescence, this has been linked previously to an increase in chitin content [22]. These findings indicate that VRC could bring about changes in the fungal cell wall that may be associated with L .…”
Section: Discussionsupporting
confidence: 72%
“…Moreover, calcofluor white staining showed that VRC-treated cells emitted a more intense fluorescence, this has been linked previously to an increase in chitin content [22]. These findings indicate that VRC could bring about changes in the fungal cell wall that may be associated with L .…”
Section: Discussionsupporting
confidence: 72%
“…The impact of the exposure of multi-metals on the cell wall of P. kudriavzevii was assessed using calcofluor white (CFW), a specific chitin dye (Costa-de-Oliveira et al 2013;Pringle 1991). Cell walls of untreated cells (control) of P. kudriavzevii, stained with CFW, displayed a weak fluorescence, while the septa (junction between the mother cell and the buds-daughter cells) displayed a bright fluorescence ( Fig.…”
Section: Multiple Metals Disturbs Membrane Integrity In a Time-dependmentioning
confidence: 99%
“…Ultrastructure analysis of C. glabrata versus C. albicans cell walls revealed ~50% more proteins, higher amounts of mannan and lower levels of total glucan in C. glabrata cell walls [20]. Conversely, C. albicans , C. tropicalis and C. parapsilosis contain higher chitin content than C. glabrata and C. krusei [21]. It has yet to be determined how or whether these cell wall differences among Candida species impact immunity.…”
Section: Phenotypic Differences Among Candida Species and Consequencementioning
confidence: 99%